Implementasi Model Talking Stick Untuk Meningkatkan Hasil Belajar Materi Keragaman Suku Bangsa, Sosial, dan Budaya Berbasis Karakter Toleransi dan Cinta Tanah Air - Retnosari, Yeni Dwi; Zainuddin, Mohammad; Muzaki, Ferril Irham (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2020)
The learning process in class still uses the lecture method, assignments, questions and answers, and skills training. This results in students getting bored easily, and teachers also have not yet instilled the value of attitude to shape character in PPKn learning. This study aims to improve student learning outcomes in PPKn subjects on ethnic, social and cultural diversity using the Talking Stick model in class IV students of SDN 02 Sukorejo Kulon. This type of research is a Classroom Action Research (CAR) with two cycles. The results obtained by the activity of the first cycle teacher 78.5%, 95% second cycle. The activity of students in the first cycle was 66.5%, the second cycle became 81%. Increased knowledge of the first cycle 63.75%, second cycle to 86%. The attitude that often arises in the first cycle is the attitude of loving the motherland, the second cycle of the attitude of cooperation and patriotism have the same number of occurrences. In the aspect of skills, in cycle II there were 8 students who received grades 4 with loud voices, the contents were delivered precisely and clearly, and there were no word errors.